2022
DOI: 10.3389/fphys.2022.928562
|View full text |Cite
|
Sign up to set email alerts
|

Myths and Misconceptions of Airway Pressure Release Ventilation: Getting Past the Noise and on to the Signal

Abstract: In the pursuit of science, competitive ideas and debate are necessary means to attain knowledge and expose our ignorance. To quote Murray Gell-Mann (1969 Nobel Prize laureate in Physics): “Scientific orthodoxy kills truth”. In mechanical ventilation, the goal is to provide the best approach to support patients with respiratory failure until the underlying disease resolves, while minimizing iatrogenic damage. This compromise characterizes the philosophy behind the concept of “lung protective” ventilation. Unfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 254 publications
0
12
0
Order By: Relevance
“…Second, we didn’t focus on the effects of spontaneous breathing on APRV. The effects of APRV with or without spontaneous breathing on ARDS patients are still being debated [ 14 ]. Third, EIT only provides a cross-sectional lung-region analysis, which may differ from whole-lung evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we didn’t focus on the effects of spontaneous breathing on APRV. The effects of APRV with or without spontaneous breathing on ARDS patients are still being debated [ 14 ]. Third, EIT only provides a cross-sectional lung-region analysis, which may differ from whole-lung evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…5 In contrast to the studies, 12,14,19 demonstrating significantly higher tidal volumes beyond the limits of lung-protective ventilation in APRV, the present study showed similar tidal volumes per PBW as well as peak pressure values compared to the matched LTV control group that followed ARDSnet recommendations. 23 However, regardless of the ventilation mode, the aim of lung protective ventilation less than or equal to the “magic number” 27 of 6 mL/kg PBW was missed in a considerable number of patients (compare Figure 1). However, there is an ongoing debate whether the ARDSnet tidal volume limitations should be applied to the APRV release volume or whether concepts of a mandatory mode of ventilation (ARDSnet) are mistakenly transferred to the paradigm of a spontaneous ventilation mode.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, time rather than pressure controls the end-expiratory lung volume. Continuous analysis of the expiratory flow curve is therefore necessary as respiratory mechanics change during ventilation, in order to accurately and independently set and adjust T High and T Low ( 100 , 104 ). If hypoxemia is present, an increase of P High then of T High are warranted.…”
Section: Adjunct Therapies and Alternative Ventilatory Modesmentioning
confidence: 99%
“…Therefore, in the absence of a large, multicenter, randomized controlled trial demonstrating a patient outcome benefit compared to low-tidal volume ventilation in patients with ARDS, a definitive recommendation for the use of APRV cannot be made ( 5 , 101 , 102 ). There have been many criticisms of APRV, regarding the difficulty of mastering this mode, the assumed risk of barotrauma, increased right ventricular afterload, or uncontrollable auto-PEEP and dynamic hyperinflation ( 104 ). However, a recent review highlighted the fact that some authors' beliefs about APRV are often based on little clinical experience with its use, and are generally not supported by rigorous studies.…”
Section: Adjunct Therapies and Alternative Ventilatory Modesmentioning
confidence: 99%
See 1 more Smart Citation